Radiative transfer of hydrogen lines from supernova remnant shock waves: contributions of 2s-state hydrogen atoms. Issue 4 (16th March 2019) - Shimoda, Jiro; Laming, J Martin
Abstract: Radiative transfer in hydrogen lines in supernova remnant (SNR) shock waves is studied taking into account the population of the hydrogen atom 2s-state. Measurements of Balmer line emission, especially of H α, are often relied on to derive physical conditions in the SNR shock. On the other hand, Lyman series photons, especially Ly β, are mostly absorbed by upstream hydrogen atoms. As a result, atoms are excited to the 3p state, and then emit H α by the spontaneous transition from 3p to 2s. Thus, the nature of H α depends on how many Ly β photons are converted to H α photons. Moreover, the Balmer lines can be scattered by the 2s-state hydrogen atoms, which are excited not only by collisional excitation but also by the Lyman–Balmer conversion. It is shown for example that the H α photons are scattered if the shock propagates into an H i cloud with a density of ∼30 cm −3 and a size of ∼1 pc. We find that the line profile of H α becomes asymmetric resulting from the difference between line centre frequencies among the transitions from 3s to 2p, from 3p to 2s, and from 3d to 2p. We also find that the broad-to-narrow ratio of H α, which is often used to estimate the ion-electron temperature equilibrium, varies at most ≃ 10 per cent depending on the ionization degree of the upstream medium because of incomplete conversion of Lyman lines to Balmer lines.